Sustainable Cacao Agritourism Development Strategy for Cau Chocolate Bali - Putu Yudika Budi Kusuma; I Wayan Agus Selamet (International Journal of Management Science and Information Technology, 2026)
While agritourism plays a crucial role in diversifying the income of cacao farmers in Bali, the sector still faces serious challenges including management inefficiencies and volatile market fluctuations. Cau Chocolate Bali is currently confronting real-world issues such as a significant decline in visitor numbers and cash flow stagnation due to suboptimal marketing strategies and a lack of innovation in tour packages. This condition creates an urgent need for strategic evaluation to ensure the destination can survive and compete in the sustainable tourism market. This study aims to formulate an agritourism development strategy for Cau Chocolate Bali using a sequential explanatory mixed-methods approach. Data were collected from 35 stakeholders through observation, in-depth interviews, and structured questionnaires, which were then analyzed using the Internal Factor Analysis Summary (IFAS) matrix, External Factor Analysis Summary (EFAS) matrix, Internal-External (IE) Matrix, and SWOT analysis. The results showed an IFAS score of 3.004 and an EFAS score of 2.513, positioning Cau Chocolate Bali in the "Growth and Build" cell (Quadrant IV). These findings indicate that while the destination possesses a competitive advantage through international organic certification, the effectiveness of digital promotion and market penetration still needs to be aggressively improved. Recommended priority strategies include strengthening digital storytelling, integrating community-based tourism, and diversifying cacao-derived products to restore the company's economic stability.